ASSESSING RADIATION PROTECTION AWARENESS AMONG HEALTHCARE PROFESSIONALS IN KHYBER PAKHTUNKHWA: A CROSS-HOSPITAL STUDY (The Research of Medical Science Review, 2024)
Background: Modern diagnostic methods often utilize ionizing radiation and it helps to identify many illnesses. Several current modalities operating on ionizing radiation comprise X-ray. Despite the fact that ionizing radiation has been used in diagnosis and therapy of various disorders it has also been linked with different avoidable risks for healthcare professional, technician and the patient. However, to minimize the risks associated with ionizing radiation, patient and personnel can be protected. This survey was conducted to establish the level of awareness of radiology staff over radiation protection.Objective: The aim of the study was to determine the awareness level of radiation protection in health care professionals practicing in diverse hospitals of KPK Pakistan.Materials and Method: Data for this cross-sectional study was collected in the various teaching hospitals in KPK Pakistan. A criteria was created in order to engage the 240 participants. The teaching hospitals that comprised were Hayatabad Medical Complex Peshawar, Lady Reading Hospital Peshawar, Timergara Teaching Hospital, and Khyber Teaching Hospital Peshawar. Questionnaire was arranged the usefulness of which is examined by carrying out a pilot study by choosing radiologic staffs from the mentioned hospitals. The data was collected simultaneously by completing the questionnaire and the data was analyzed with aid of the SPSS software.Results: The educational background of 240 participants differed from SSC (matric) to graduation/ ‘F’ level. The professional practice durations of the participants in medical radiology mean ± SD was 15 ± 8 years; The duration of practice ranged between 1-32 years. Finally the data are considered to assess that the participants’ knowledge level about radiation awareness was different from each other the range was 35 % to 95% and the median score of the participants was 75 % of total marks. It emerged that the awareness level difference depends on the educational background and duration of experience in the specialty of medical radiation science profession.Conclusion: The survey finding revealed the existence of a very strong need to implement personnel training programme in MRS both at provincial and national level. In addition, one needs the right educational qualifications in science and practice of administering personal qualities assessment (PQA) tests on the radiology personal when recruiting them.